Application of the theory of interceptor-protector action to in vitro biological experiment - Buchelnikov, A. S.; Rubakina, V. A.; Mosunov, A. A.; Evstigneev, M. P. (Biophysical Bulletin, 1970)
The purpose of this paper is to ascertain whether the theory of interceptor-protector action (IPA) can be appliedto quantitation of the so far published data of biological experiments in vitro regarding the cases when differentDNA-binding ligands are administered simultaneously. The basic assumptions of the IPA theory were clearly formulated. Two different ways for estimation of biological effect were considered (viz. point estimation and estimation using concentration dependence of the AD factor). It was found that the IPA theory agrees with data from mutagenic test and the data from the experiment in proliferating cell lines